Gilang ramadhan ANALISIS PEMASARAN GREEN BEAN KOPI ROBUSTA (Coffea Canephora) DI DESA SUMBER SARI KECAMATAN KABAWETAN KABUPATEN KEPAHIANG - Gilang; Darwan Effendi, Regi Fernandez, Bayu Cahya Ningrat (PUCUK : Jurnal Ilmu Tanaman, 2025)
This study aims to analyze the marketing channels and calculate the costs, margins, and profits of green bean robusta coffee marketing in Sumber Sari Village, Kabawetan District, Kepahiang Regency. Robusta coffee is a plantation commodity with high economic value and plays a crucial role in the local economy. This research used a descriptive quantitative method, collecting data through interviews, observation, and documentation involving 20 farmers and 5 coffee collectors. The findings revealed one main marketing channel: from farmers to local collectors and then to other village collectors. This marketing structure is simple and efficient. The average selling price at the farmer level was Rp72,000/kg, while the consumer-level price reached Rp85,000/kg. The total marketing margin was Rp13,000/kg, with a marketing cost of Rp6,000/kg and a net profit of Rp7,000/kg. The farmer’s share reached 85.71%, indicating that farmers still gain a significant portion of the profit. This system’s advantage lies in cost efficiency, as collectors directly collect the harvest from the farmers. Furthermore, farmer characteristics such as productive age, over six years of farming experience, and land ownership between 1–2 hectares contributed to marketing success. It is recommended that farmers improve product quality and strengthen institutions such as cooperatives to enhance bargaining power. With a straightforward distribution system and the active role of collectors, the green bean robusta coffee marketing in Sumber Sari Village is considered effective and profitable. Keywords: robusta coffee, green bean, marketing, margin, cost, profit